Optimasi penambahan karagenan dan minyak asiri bawang putih pada edible coating dengan response surface methodology: Optimization of kappa carrageenan and garlic essential oil addition in edible coating using response surface methodology - Nurdiani, Rahmi; Firdaus, Muhamad; Astuti, Retno Tri; Yasmin, Putri; Fauzi, Adnan; Ningsih, Omega Tantia; Puspitasari, Dwi Anggraini; Delima, Meita Putri (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Protein-based edible coatings, such as gelatin, can help preserve product quality and extend shelf life while also serving as carriers for bioactive additives. The addition of kappa carrageenan enhanced the strength and stability of the coating, whereas garlic essential oil improved its antioxidant and antimicrobial properties through the presence of allicin and phenolic compounds. This study aimed to optimize the addition of carrageenan and garlic essential oils to produce edible coatings with optimal antioxidant and antimicrobial activities. The experimental method used Design Expert software version 13 with two factors: kappa carrageenan (0.7–1.3 g) and garlic essential oil (0.9–1.5 mL). Results showed that the best antioxidant and antimicrobial responses were obtained with 1.2 g of carrageenan and 1.4 mL of garlic essential oil, resulting in an antimicrobial response of 3.71 mm against Escherichia coli and 4.75 mm against Staphylococcus aureus, with an antioxidant activity of 57.5%. The highest amino acid content in catfish gelatin was glycine at 261,366.93 mg/kg, L-proline at 122,232.03 mg/kg, and L-arginine at 92,390.47 mg/kg. The addition of carrageenan and garlic essential oil enhances the antioxidant and antimicrobial activities of edible coatings, making them promising eco-friendly alternatives for active packaging.